FAMILY AND FAMILY CATECHESIS IN EUROPE TODAY. A MATTER OF DIVERSIFICATION - Lombaerts, Herman; Osewska, Elzbieta (Acta Paedagogica Vilnensia, 2008)
It is the intention of this contribution to explore various aspects of the situation of the family in Europe today: understanding the family. The understanding of the family in analysed in terms of a dynamic approace (the changing family, the family as a system providing philosophical presuppositions as well as the relationship of a person and a family. In a second part we intend to reconsider the contribution of catechesis to family in contemporary European context: diversifications and catachesis, models of family catechesis.
Keywords: family; family catechesis; society; religion; christianity